Progenitor cell expansion: an important source of hepatocyte regeneration in chronic hepatitis - Eleazar, Jennifer A.; Memeo, Lorenzo; Jhang, Jeffrey S.; Mansukhani, Mahesh M.; Chin, Steven; Park, Soo Mi; Lefkowitch, Jay H.; Bhagat, Govind (Journal of hepatology, 2004)
Progenitor cell activation with subsequent maturation to hepatocytes and cells of the biliary lineage has been demonstrated in a variety of chronic liver diseases but the kinetics and magnitude of the progenitor cell response has not been adequately studied in detail in chronic hepatitis. We undertook this study to evaluate factors responsible for the progenitor cell/ductular response and further dissect the role of disease grade and stage as determinants of hepatocellular differentiation of bipotential progenitor cells in chronic hepatitis. Cytokeratin 7 (and 19) stained biopsies from patients with chronic hepatitis C ( n=47), hepatitis B ( n=20), and autoimmune hepatitis ( n=20) were studied. Ploidy analysis and proliferation indices were evaluated in a subset of cases. Ductular reactions were present in the majority of cases (97%), appeared early in disease, and correlated with disease activity, while progenitor cell derived hepatocyes appeared later in disease and their extent correlated with disease stage. Proliferation indices of all cell types correlated with disease activity. Progenitor cell derived hepatocytes accrue in chronic hepatitis, possibly related to native hepatocellular dysfunction. However, the fate of these hepatocytes is unclear.